Strategi Daerah Istimewa Yogyakarta Sebagai Tempat Wisata Kesehatan Pelayanan Medis Di Indonesia - Yanuria Jayanti (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
Health tourism is an activity journey tour To get service Health. Yogyakarta is Wrong One province owns potency in the development of health tourism. this _ seen Yogyakarta recorded owner House Sick type A has 11 5 star hotels that provide spa and fitness. However moment this is health tourism yet Lots realized And Not yet developed in Yogyakarta. The objective of the study This is To know the components development of health tourism and know the strategy development of health tourism. Medical Tourism as part of Strategy Marketing House Sick in Tourism Area. An article in reviews, This is that explained Medical Tourism and strategy marketing hospital in Indonesia. House Sick as a business private use various strategy to attract more Lots patient or customers, like creating room therapy in a hybrid hotel (home-designed pain _ For comfort patient international ). House Sick also compose strategy marketing For direct patient And customer as well as identify three strategies the is with connect to patient potential through a visit to the country origin , employ intermediary journey medical And compiling 'medical check-up' packages for healthy people